PENGARUH HABITS OF MIND (KEBIASAAN BERPIKIR) TERHADAP PEMECAHAN MASALAH MATEMATIK SISWA SMP - Nuni Nurmala; Euis Eti Rohaeti; Ratna Sariningsih (Departement of Mathematics Education, 2019)
Problem solving is identical to learning mathematics because every student learning inevitably prompted work onreserved to measure the student's ability. The purpose of this research is to know the student's problem solving abilities. The method used is descriptive qualitative methods Researchers acted as observer, giving the question of tests and question form on the students. Test instrument in the form of descriptions and question form Habits Of Mind (habits). The subject of research that is grade VII. Researchers using an indicator of problem solving: understanding the problem, devise a plan of resolution, carry out the plan of settlement, check back. From the results of the tests given. Habits Of Mind affects the student's problem solving ability and the students is hampered in its execution completion indicators and check back for answers.